Essentials of pediatric nutrition - King, Kathy , 1969-; Samour, Patricia Queen (Burlington, Massachusetts : Jones & Bartlett Learning, 2013)
Abridged version of: Pediatric nutrition / edited by Patricia Queen Samour, Kathy King. 4th ed. c2012
1. Prenatal nutrition -- 2. Physical growth -- 3. Assessment basics -- 4. Premature infant nutrition -- 5. Infant nutrition -- 6. Normal nutrition after infancy -- 7. Food hypersensitivities -- 8. Weight management -- 9. Inborn errors of metabolism -- 10. Developmental disabilities -- 11. Pulmonary diseases -- 12. Gastrointestinal disorders -- 13. Kidney disease -- 14. Cardiology -- 15. Diabetes -- 16. HIV and AIDS -- 17. Oncology and sickle cell disease -- 18. Nutrition in burns -- 19. Enteral nutrition -- 20. Parenteral nutrition -- 21. Botanicals
Abridged version of: Pediatric nutrition / edited by Patricia Queen Samour, Kathy King. 4th ed. c2012
Includes bibliographical references and index
Keywords: Child; Child Nutrition Disorders; Child Nutritional Physiological Phenomena; Diet therapy; Infant; Infant Nutrition Disorders; Infant Nutritional Physiological Phenomena; Needs Assessment